SKILLS MONITORING IN HEALTHCARE STUDIES – FOR PATIENT SAFETY AND HEALTHCARE QUALITY - Slavinska, Andreta; Grigorovica, Evita; Palkova, Karina; Jansone-Ratinika, Nora; Silis, Matiss; Sabeļņikovs, Oļegs; Pētersons, Aigars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The competence of healthcare professionals is crucial in ensuring patient safety and the quality of healthcare. Skills are one of the most important aspects of competence, but often health care employers, when assessing the readiness of young professionals, point out that the ability to implement skills in a real work environment are unclear, insufficient and even inadequate.The paradigm shift in education intends bringing skills to the foreground. In order to promote skills management, Rīga Stradiņš University (RSU) already in 2016 started work on the institutional level project “Skills Monitoring System” (hereinafter - SMS), focusing primarily on work and profession specific skills in the field of health care studies.Visible and demonstrable monitoring of skills in education is an innovation. The aim of this article is to analyze and reflect the coherence of the RSU Skills Monitoring System concept with the current principles of education policy development, legal framework and basic principles of higher education pedagogy in skills acquisition and evaluation in health care education, as well as to evaluate the initial results of the newly developed system.In order to achieve the goal, an interdisciplinary, qualitative study was conducted, where analytical and descriptive, inductive, deductive and synthesis research and legal (translation) norm methods were implemented, as well as interviews to evaluate initial results.The results of the research show that the components and solutions included in SMS have been developed in accordance with the legal framework and the main educational guidelines, in accordance with the theoretical concepts of pedagogy. An education approach based on simulation integrated in the acquisition of skills allows to systematically evaluate the amount and quality of theoretical knowledge, to determine the actual level of abilities and to predict the quality of performance and compliance with the real work environment. The management of skills acquisition in Higher Education Institutions should be supported and promoted from the point of view of educators, employees and sectoral professional associations and employers.